Different sources of resistance in soybean against soybean aphid biotypes - Chandran, Predeesh (Kansas State University, 2010)
The soybean aphid, Aphis glycines Matsumura, arrived first to North America during the midst of 2000. It is a very fast spreading insect and causes a high yield loss of above 50% in most of the soybean growing tracts of United States. Another important economic threat is it’s ability to transmit some viruses to soybean. Studies to control this exotic pest started early during the year of its arrival. But a complete integrated pest management (IPM) approach that includes a combination of different control measures has yet to be completely developed. Host plant resistance is one component of integrated pest management and is more sustainable than any other control methods against this insect. In the first study, more than 80 genotypes were screened with two given aphid biotypes, biotype 1 and biotype 2. It was found that the genotypes that were earlier resistant to biotype 1 (K1639, K1642, K1613 K1621, Dowling and Jackson) were susceptible to the new biotype 2 with large populations developing on these genotypes. But we found three new Kansas genotypes that showed resistance only against biotype 1, but not against biotype 2. However, the two of the Michigan genotypes (E06902 and E07906-2) showed resistance to both biotype 1and biotype 2. In second study, the feeding behavior analyses of aphid biotypes were done using the EPG, Electrical penetration graph, technique for a recorded 9 hrs probing time. The resistant and susceptible genotypes show significant differences in their EPG parameters, especially for the sieve element duration in both biotypes. Most of the aphids reached sieve element phase (> 90%) in susceptible genotypes, but only few (<30%) were reached in resistant genotypes. But, no differences were found in any other probing phases between resistant and susceptible genotypes, except the number of potential drops (PDs) in biotype 2. Thus, it is concluded that resistance is largely associated with phloem tissues and there could be some biochemical, physical or morphological factors that affect the stylet penetration in aphids.
Keywords: Soybean aphid; Biotype; Electrical Penetration Graph; Agriculture, General (0473); Agriculture, Plant Culture (0479)